Using Differentiated Waste Fees to Encourage the Sustainable Recycling of Organic Waste - Friege, Henning; Hentschel, Maike (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
The valorisation of household and commercial bio-waste into soil improvers helps to reduce disposable waste, mitigate climate change, and improve soil resilience. While the separate collection of bio-waste is mandatory in the European Union, this remains a challenging task, particularly for large cities, due to quality problems in densely populated areas. In addition to various informational and motivational tools for households, financial incentives are becoming increasingly important. However, there is a lack of robust evidence regarding the optimal use of these incentives and their impact on the quantity and quality of collected bio-waste. We investigated the impact of different charging systems on the quantity and quality of bio-waste, basing our research on the experiences of more than twenty European cities and using a detailed questionnaire completed by the relevant administrators. The results confirm that cities, which provide financial incentives for waste sorting, yield a higher quantity of separated bio-waste. As introducing tiered fees can lead to quality issues, monitoring bio-waste and taking action against polluters seems to be unavoidable. Since the identification of polluters is very difficult in the case of multi-family homes, the results are discussed with a special focus on densely populated cities. Pilot projects for alternative options for the valorisation of organic waste, particularly in districts with high-rise buildings, should be evaluated.
Keywords: Bio-waste; Compost; Charging System; Waste Collection; Green Waste; Food Waste; Polluter-Pays Principle